1990
DOI: 10.2134/jeq1990.00472425001900010011x
|View full text |Cite
|
Sign up to set email alerts
|

Pine Growth Variation Associated with Overburden Rock Type on a Reclaimed Surface Mine in Virginia

Abstract: This study was designed to compare the effects of two overburden spoil types and various mixtures of the two spoils on the performance of pitch × loblolly hybrid pine (Pinus × rigitaeda). Sandstone and siltstone overburden were used to create five rock mix treatments: pure sandstone (SS), pure siltstone (SiS), a 2:1 SS/SiS mix, a 1:1 SS/SiS mix, and a 1:2 SS/SiS mix. Tree survival was not affected by rock mix, but growth was greatly affected. The greatest growth response occurred on the SS treatment and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 0 publications
3
55
1
2
Order By: Relevance
“…Contudo, nas duas camadas avaliadas, a APD foi menor na testemunha e maior no CalcBbCa, o que pode estar refletindo o efeito da cama de aviário na retenção de água. A compactação e a baixa disponibilidade de água para as plantas são os principais problemas constatados em solos reconstruídos após mineração (Torbert et al, 1990). O aumento da densidade do solo oriundo de reconstrução diminui a infiltração da água e aumenta o escoamento superficial no perfil compactado (Harms & Chanasyk, 2000).…”
Section: Resultsunclassified
“…Contudo, nas duas camadas avaliadas, a APD foi menor na testemunha e maior no CalcBbCa, o que pode estar refletindo o efeito da cama de aviário na retenção de água. A compactação e a baixa disponibilidade de água para as plantas são os principais problemas constatados em solos reconstruídos após mineração (Torbert et al, 1990). O aumento da densidade do solo oriundo de reconstrução diminui a infiltração da água e aumenta o escoamento superficial no perfil compactado (Harms & Chanasyk, 2000).…”
Section: Resultsunclassified
“…Only later was it determined that tree growth was quite variable on sites with differing mine soils (Andrews et al, 1992;Ashby et al, 1984;Daniels and Amos, 1984;Johnson and Skousen, 1995;Rodrigue and Burger, 2004;Torbert et al, 1990;Zeleznik and Skousen, 1996). Recent research has indeed verified tremendous differences in tree growth in different spoil types placed at the surface as rooting media.…”
Section: Early Reforestation Of Surface Minesmentioning
confidence: 99%
“…Researchers have reported on the attributes of loose-graded brown weathered sandstone spoil compared to un-weathered fine-textured rocks (Torbert et al, 1990). Other studies have identified certain types of loose-graded mixed un-weathered sandstone and shale (mine run) spoil as being highly productive (Conrad et al, 2002;Angel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%